QUALITY OF LIFE OF PATIENTS AFTER TOTAL KNEE ARTHROPLASTY - Music, Kenan; Pelicic, Damir; Konatar, Ranka; Maras, Borko (Sanamed, 2025)
Introduction: Diseases of the musculoskeletal system are common in the general population. They significantly contribute to increased morbidity, more frequent use of healthcare services, reduced working capacity, increased professional absences, and the occurrence of disability. Methodology: This study involved patients who underwent knee replacement surgery at the Clinical Center of Montenegro, Podgorica. We employed the SF-36, a widely used universal standard questionnaire, which has been applied in over 4,000 published studies. Results: Statistically significant improvements in quality of life were observed in all examined domains: physical functioning (p=0.0001), role limitations due to physical problems (p=0.0001), role limitations due to emotional problems (p=0.0001), vitality/energy (p=0.0002), mental health (p=0.0004), social functioning (p=0.0001), physical pain (p=0.0001), and perception of general health (p=0.0001) following knee endoprosthesis implantation. Conclusion: Statistically significant differences were observed in all quality of life domains before and after knee endoprosthesis surgery, confirming the improvement in patients’ quality of life after the procedure.